Actively targeted chitosan-based vector for efficient CRISPR-Cas9 mediated Tenascin-C gene editing in triple negative breast cancer - Bareke, H.; Fuentes, M.; Oladipo, A. A.; Ozbas, S.; Salva, E. (Mary Ann Liebert, Inc, 2021)
[Abstract Not Available]
European-Society-of-Gene-and-Cell-Therapy Collaborative Virtual Congress (ESGCT) -- OCT 19-22, 2021 -- ELECTR NETWORK